2017
DOI: 10.1039/c7sc00223h
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide–carbon nanotube hybrid assemblies: cooperatively strengthened OH⋯OC hydrogen bonds and the removal of chemisorbed water

Abstract: The effective removal of chemisorbed water in graphene oxide by oxidized carbon nanotubes via cooperatively strengthened OH···OC hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 48 publications
4
28
0
Order By: Relevance
“…These XRS observations are in agreement with the physical-chemical characterization of the GO papers. Indeed, XPS and TGA results (see supporting information) confirm the removal of OFGs and bound water (Stankovich et al, 2007;Nú ñ ez, 2015;Nú ñ ez et al, 2017) in the temperature range between 403 and 533 K.…”
Section: Thermal Treatment Of Go Papermentioning
confidence: 57%
See 1 more Smart Citation
“…These XRS observations are in agreement with the physical-chemical characterization of the GO papers. Indeed, XPS and TGA results (see supporting information) confirm the removal of OFGs and bound water (Stankovich et al, 2007;Nú ñ ez, 2015;Nú ñ ez et al, 2017) in the temperature range between 403 and 533 K.…”
Section: Thermal Treatment Of Go Papermentioning
confidence: 57%
“…The thermal reduction of GO, which allows tuning of its opto-electronic properties, induces the removal of water as well as OFGs with a partial restoration of sp 2 carbon bonds, and also the removal of carbon atoms from the GO plane, introducing new structural vacancies throughout the graphene sheets (Gao et al, 2009;Pei & Cheng, 2012). It has been suggested that water may play a significant role in the irreversible decomposition of OFGs during the reduction process of GO under thermal treatment (Acik et al, 2010;Nú ñ ez, 2015). Therefore, study of the intercalated water in GO as a function of temperature can provide valuable information for the understanding of the thermal reduction process of GO.…”
Section: Introductionmentioning
confidence: 99%
“…34 The sol-gel approach starting from GO is a very cost-effective and versatile method which can also benefit from the rich surface chemistry of GO [35][36][37] for doping or forming hybrids. 38 Moreover, this method allows moulding the macroscopic shape to that of the container. Other techniques such as wet spinning 8 , electrospinning 39 or 3-D printing 40 of GO dispersions have been also used to prepare aerogels with specific macroscopic morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…GO, a chemically derived sheet of graphene decorated with oxygen containing functional groups on its basal plane and edges, was chosen due to its promise as chemically tunable platform for optoelectronic applications and its unique ability to act as an amphiphilic macromolecule . GO thus is ideally suited to self‐assemble hierarchical GO structures, such as GO films and papers, as well as to complex with many organic materials. In combination with conjugated polymers GO reveals its value as acceptor material and provides enhanced conducting and charge‐transfer properties .…”
Section: Introductionmentioning
confidence: 99%